Copper-Catalyzed Chemoselective Nitro Reduction - Le, Thi Minh Thi; Zhong, Mingbing; Jubault, Philippe; Poisson, Thomas (Synthesis, 2024)
The reduction of nitro compounds into the highly valuable anilines is reported using a Cu catalyst and B2Pin2. The reactions proceed under very mild conditions and showcase excellent functional group tolerance. This method is applied to a large panel of nitro derivatives, including biorelevant molecules and important synthetic intermediates, toward the synthesis of active pharmaceutical ingredients (APIs). This novel reaction manifold intends to provide a complementary approach to the existing portfolio of nitro-reduction methods.
Keywords: nitro group; aniline; reduction; copper; boryl radicals